2009
DOI: 10.1007/s00192-009-0853-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle function in women presenting with pelvic floor disorders

Abstract: Although most women with pelvic floor disorders are familiar with PMEs, less than one fourth could perform adequate contractions at the time of initial evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 13 publications
3
21
0
5
Order By: Relevance
“…Moen et al [12] found that women with advanced age and high parity had lower scores during the evaluation, which agrees with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moen et al [12] found that women with advanced age and high parity had lower scores during the evaluation, which agrees with our study.…”
Section: Discussionsupporting
confidence: 93%
“…In relation to the scale, scores of 2.0 refer to low-intensity contraction with little sustainment. According to the literature, patients who reach values of 3.0 onwards, without recruitment of other muscle groups, present proper muscle contraction [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with an adequate PF contraction should be given at least a 3 on the scale [20]. In our study, pregnant women presented less muscle strength than nonpregnant women (p<0.05).…”
Section: Resultsmentioning
confidence: 59%
“…Apesar de a maioria das mulheres com desordens do assoalho pélvico ser familiarizadas com exercícios nessa região, menos de 25% são capazes de realizar adequada contração (com grau de força de três a cinco, de acordo com a escala de Oxford, e sem recrutar outros grupos musculares durante a contração), o que mostra associação de desordens e pobre função muscular do assoalho pélvico (16,17).…”
Section: Resultsunclassified